Magnetostriction and magnetostructural domains in CoTiO3 - Dey, Kaustav; Hoffmann, Marco; Klingeler, Rüdiger (Arxiv, 2021)
We report the magnetostrictive length changes of CoTiO3 studied by means of high-resolution dilatometry in magnetic fields (B) up to 15 T. In the long-range antiferromagnetically ordered phase below TN = 38 K, the easy-plane type spin structure undergoes a spin-reorientation transition in the ab plane in magnetic fields B||ab ≈ 2 T. We observe pronounced length changes driven by external magnetic field in this field region indicating significant magnetoelastic coupling in CoTiO3. ...
Artikel datiert vom 27. September 2021
Gesehen am 09.01.2024